The role of groundwater flow in controlling the arsenic concentration in the southern part of the Great Hungarian Plain - Varsányi Irén (Acta mineralogica-petrographica, 2005)
Concentrations of main and microelements and humic substances were determined in 456 subsurface water samples in the Great Hungarian Plain (central part of the Pannonian Basin). The lack of correlation between arsenic and other chemical components in the bulk of the samples, and the geographical and depth distributions of arsenic suggest that processes influencing the arsenic content should be studied in separate water flow systems. It was established that in the different parts of the groundwater flow line different factors play a role in controlling the arsenic content of waters. In the discharge regions of the water flow systems humic substances are the main controlling factors of mobilization of arsenic. In the recharge area association of arsenic and iron indicates adsorption or co-precipitation of arsenic on ferric oxides and hydroxides.